Methanol amination over hydrothermally treated zeolites RHO and Modernite - Van Steen, Linda Heather Callanan (Department of Chemical Engineering, 2017)
Methylamines are important chemicals in many industrial processes. They have use as intermediates for the production of many compounds containing amino groups as well as being used on their own. The acid catalysed amination of methanol generally yields a thermodynamically controlled product distribution. The equilibrium distribution for mono-, di-, and trimethylamine (MMA, DMA, and TMA), at 325°C and a molar methanol to ammonia ratio of 1, is 17, 21, and 62 mol % respectively. The market demand, on the other hand, is for about 33, 53, and 14 mol % MMA, DMA and TMA. Industrially, methylamines are formed by the reaction of methanol or dimethyl ether and ammonia over amorphous silica-alumina. This process involves large separation and recycle units which are both costly and energy intensive as the separation requires azeotropic distillation at 15 bar. Methylamines can be formed over other solid acid catalysts with definite crystal structures, namely zeolites. While being more active than amorphous silica-alumina, most zeolites do not show improved selectivity. Catalysts, which have, however, been reported to show improved selectivity to DMA, include zeolites Rho, ZK-5 and Chabazite. In addition, certain forms of hydrothermally treated Mordenite can produce nonequilibrium product distributions. The performance of Rho can also be improved with hydrothermal treatment. The objectives of this study were briefly as follows. Firstly, the question was asked as to which of the catalysts studied, viz. Rho and Mordenite, was the most suitable for the methanol amination reaction. The second objective was to find the optimal performance achievable from any catalyst using hydrothermal treatment. The third, and possibly most important, objective was to propose reasons for the changes caused to each catalyst by hydrothermal treatment.